Análisis a los sistemas eléctricos de la cartonera Marcasa. - Cuenca Alulima, Carlos Aníbal (2007)
The industrial sector of our country is the main generator of direct and indirect jobs, and it is the largest consumer of electricity so it is vital to perform electro-energy audits and identify potential savings potential. This research is a methodology to perform audits to electrical systems, from a series of concepts, theoretical foundations, standards and safety rules and calculation methods required in the audit and to determine the potential savings. The study was the development in the industrial sector, specifically in the cardboard factory "MACARSA" in the city of Machala, where the uprising line diagram of the plant, an inventory of all electrical receivers as well as the measurements was conducted key figures in the electrical distribution system of the company. The study was conducted in three specific parameters: Redesign line diagram of the plant; history analysis of electricity consumption for the last twelve months; study load factor transformer substations. To determine the actual consumption of the factory a network analyzer (A2000) I was used, the same one that allowed us to present a plan for energy saving measures.